Fame da morire. Due casi clinici e una nuova ipotesi etiologica - Cagna, Pamela (Metapsychologica - rivista di psicanalisi freudiana, 2023)
The self-preservation drives are, for Klein, Lefort and Lacan not true drives and do not play any significant role in the psychological genesis of the subject. However as it is undeniable that ongoing starvation has profound physical effects to the point of causing permanent damage to the organs, it is difficult to think that this type of processes wouldn’t lead to a psychological relapse, above all if the extended state of deprivation occurs in the very early stages of children’s existence. In light of Freudian self-preservation theories, of anaclisis (Anlehnung) and of the creation in stages of the subject, it is necessary to reinterpret two famous cases of infantile pathology.